2020
DOI: 10.1007/s00330-020-07041-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of interventional radiology activity in a large metropolitan Italian tertiary care hospital: how the COVID-19 pandemic emergency has changed our activity

Abstract: Objectives To retrospectively analyze interventional radiology (IR) activity changes in the COVID-19 era and to describe how to safely and effectively reorganize IR activity. Methods All IR procedures performed between January 30 and April 8, 2020 (COVID-era group) and the same 2019 period (non-COVID-era group) were retrospectively included and compared. A sub-analysis for the lockdown period (LDP: 11 March-8 April) was also conducted. Demographic, hospitalization, clinical, and procedural data were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
2
25
0
1
Order By: Relevance
“…As noted with prior studies [ 2 5 ], the LDP induced an overall reduction in the number of elective IR procedures, with a relative increase in emergency procedures. The present study showed that this interruption in IR procedures may have a negative impact for liver oncology patients.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…As noted with prior studies [ 2 5 ], the LDP induced an overall reduction in the number of elective IR procedures, with a relative increase in emergency procedures. The present study showed that this interruption in IR procedures may have a negative impact for liver oncology patients.…”
Section: Introductionsupporting
confidence: 78%
“…The lockdown period (LDP) due to the Covid-19 pandemic was declared in Portugal from the 18 March until the 2 May 2020 [ 1 ], causing a reduction/suspension in non-urgent medical care during this period. Previous studies have confirmed the negative impact of the LDP in the workload at different Interventional Radiology (IR) units across Europe [ 2 , 3 ]. However, the potential impact on disease progression for oncology patients scheduled for loco-regional therapies (LRT) is mainly unknown, hence this report, which is a single-centre retrospective analysis on the impact of Covid-19 pandemic in an IR Unit.…”
Section: Introductionmentioning
confidence: 93%
“…Some studies have shown that the overall workload in IR has suffered less from pandemic-related shutdown than for the total hospital workload [5]. This study showed that IR procedures performed on trauma patients during the first wave in Melbourne increased by 25%.…”
Section: To the Editormentioning
confidence: 65%
“…A study published by Lezzi et al reported a 48% overall workload reduction due to the COVID-19 pandemic. 14 Neurointerventions were among the least affected, as most of these procedures fall under emergencies such as stroke, SAH, and intracerebral hemorrhage. Neurointerventional procedures such as stroke thrombectomy and endovascular therapy for ruptured aneurysm increased marginally (31%, p = 0.409 and 14%, p = 0.625, respectively).…”
Section: Resultsmentioning
confidence: 99%